General geology and flood risk analysis in Sg. Sam, Kuala Krai, Kelantan using remote sensing and GIS technique - Naimah Abd Malek (2018)
The research was conducted at Sungai Sam, Kuala Krai, Kelantan entitled General Geology and Flood Risk Analysis Using Remote Sensing and GIS Technique. The study area covers about 25 km2. The objectives of the research are 1) to produce geological map of Sg. Sam, Kuala Krai, Kelantan with 1: 25 000 scale ratio, 2) to produce ﬂood risk area map of Sg. Sam, Kuala Krai, Kelantan by using ArcGIS soﬂware and 3) to correlate ﬂood risk area map with land cover changes. Fieldwork studies were carried which requires a speciﬁc observation and measurement towards each different lithology found in study area through traversing and sampling. Laboratory analysis is done by observing and analyzing the thin section of sample rock under microscope. Result shows three different rocks unit in study area. The lithogies found are limestones, soundstone, silstone, shale, mudstone, tuffs and phyllite. The geological map is produced, revealing different areas for each different lithological unit. It is essential for geologist for various purpose including provide an updated geological infonnation to reduce death and damage done by geologic hazards. The ﬂood risk area map consists of particular level is produced based on a few parameters such as accuracy of Digital Elevation Model, water level, ﬂood depth and amounts of rainfall. Landsat image of pre-ﬂooding and post- ﬂooding are obtained to analyze the ﬂood occurrence. Flood risk analysis is made by correlating flood risk area (low, medium and high) with land cover changes.